Evaluation of orthodontic tooth movement by 3D micro-computed tomography (µ-CT) following caffeine administration - H. Herniyati; Happy Harmono; Leliana Sandra Devi; Sri Hernawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2019)
Background: The compressive strength of orthodontic tooth movement will be distributed throughout the periodontal ligament and alveolar bone, resulting in bone resorption on the pressure side and new bone formation on the tension side. Caffeine, a member of the methyl xanthine family, represents a widely-consumed psychoactive substance that can stimulate osteoclastogenesis through an increase in RANKL. A 3D Micro-Computed Tomography (µ-CT) x-ray device can be used to measure orthodontic tooth movement and changes in periodontal ligament width. Purpose: The purpose of this research was to analyze the effects of caffeine on the distal movement distance of two mandibular incisors using 3D µ-CT. Methods: The research subjects (guinea pigs) were randomly divided into four groups. Of the two control groups created, one received two weeks of treatment and the other three weeks. The members of these two control groups were subjected to orthodontic movement but received no caffeine. Meanwhile, the other two groups were treatment groups whose members also received either two or three weeks of treatment. In these two treatment groups, the subjects were subjected to orthodontic movement and received a 6 mg/500 BM dose of caffeine. The orthodontic movement of the subjects was induced by installing a band matrix and orthodontic bracket on each mandibular incisor to move distally by means of an open coil spring. Observations were then conducted on days 15 and 22 with µ-CT x-rays to measure the distal movement distance of the two mandibular incisors and the width of the periodontal ligament. Results: The administration of caffeine increased the tooth movement on day 15 (p<0.05) and day 22 (p<0.05). The increase in the tooth movement on day 22 was greater than that on day 15 (p<0.05). The width of the periodontal ligament on the pressure side of the treatment groups experienced greater narrowing than that of the control groups (p<0.05). Meanwhile, the width of periodontal ligament on the tension side of the treatment groups widened more than that of the control groups (p<0.05). Conclusion: µ-CT x-ray can be used to evaluate the extent of orthodontic movement in addition to the width of the mandibular incisor periodontal ligament during orthodontic tooth movement. Moreover, it has been established that the administering of caffeine can improve orthodontic tooth movement.